Catalytic Denitrification in a Trickle Bed Reactor: Ion Exchange Waste Brine Treatment. Issue 5 (1st May 2017) - Bergquist, Allison M.; Bertoch, Madison; Gildert, Gary; Strathmann, Timothy J.; Werth, Charles J.
Abstract : Catalytic reduction of nitrate in ion exchange (IX) waste brine for reuse is a promising option for reducing IX costs and environmental impacts. A recycling trickle bed reactor (TBR) was designed and optimized using 0.5 percent by weight (wt%) palladium–0.05 wt% indium catalysts supported on US mesh size 12 × 14 or 12 × 30 activated carbon particles. Various liquid superficial velocities (Ur ) and hydrogen gas superficial velocities (Ug‐H2 ) were evaluated to assess performance in different flow regimes; catalyst activity increased with Ug‐H2 at all Ur for both catalysts and was greatest for the 12 × 30 catalyst at the lowest Ur (8.9 m/h). The 12 × 30 catalyst demonstrated up to 100% higher catalytic activity and 280% higher mass transfer rate compared with the 12 × 14 catalyst. Optimal TBR performance was achieved with both catalysts in the trickle flow regime. The results indicate that the TBR is a promising step forward, and continued improvements are possible to overcome remaining mass transfer limitations.